Analytical Hierarchy Process (AHP):A Steady Method for Quality Decision Making: A Case Study in Snack Food Industry (Journal of Pharmaceutical Negative Results, 2022)
If several hours pass between meals and blood glucose levels fall, snacks are the supplement that gives you an energy boost. It assists in reducing appetite and avoiding overeating at the subsequent meal. When choosing particular snacks like fresh fruit or nuts, it also provides additional nutrients. Over the years, the snacking business has undergone significant development, emerging as one of the promising industries contributing to the expansion of the national economy. Faced with increasingly aware, discerning and demanding costumers I have applied a multi-criteria decision-making methodology that is Analytical Hierarchy Process (AHP) to meet the best needs of industrialists as well as costumers. Thus, the objective of this work is to determine the bestselling snack company.